The Spirit in the Book of Revelation - Waddell, Robby, (Journal of Pentecostal Theology Supplement Series ;, 2006)
The investigation centres on the role of the Spirit in Revelation, which the author considers is best defined as the Spirit of Prophecy. A survey of scholarship on the pneumatology of the Apocalypse is followed by a study of intertextual connections. The author's own religious context within Pentecostalism then informs a possible hermeneutic that is faithful to the ethos of the movement. Biblical and literary studies are situated within the context of a Pentecostal community as attention is paid to the prophecy concerning the temple and the witnesses in Rev 11. This key passage is shown to form the theological as well as the literary centre of the Spirit's role in Revelation.